Increased Sestrin3 Contributes to Post-ischemic Seizures in the Diabetic Condition - Shi, Zhongshan; Lei, Zhigang; Wu, Fan; Xia, Luoxing; Ruan, Yiwen; Xu, Zao C. (Frontiers in Neuroscience, 2021)
Seizures are among the most common neurological sequelae of stroke, and diabetes notably increases the incidence of post ischemic seizures. Recent studies have indicated that Sestrin3 (SESN3) is a regulator of a proconvulsant gene network in human epileptic hippocampus. But the association of SESN3 and post-ischemic seizures in diabetes remains unclear. The present study aimed to reveal the involvement of SESN3 in seizures following transient cerebral ischemia in diabetes. Diabetes was induced in adult male mice and rats via intraperitoneal injection of streptozotocin (STZ). Forebrain ischemia (15 min) was induced by bilateral common carotid artery occlusion, the 2-vessel occlusion (2VO) in mice and 4-vessel occlusion (4VO) in rats. Our results showed that 59% of the diabetic wild-type mice developed seizures after ischemia while no seizures were observed in non-diabetic mice. Although no apparent cell death was detected in the hippocampus of seizure mice within 24 hours after the ischemic insult, the expression of SESN3 was significantly increased in seizure diabetic mice and rats after ischemia. The post-ischemic seizure incidence significantly decreased in SESN3 knockout mice. Furthermore, all diabetic rats suffered from post-ischemic seizures and non-diabetic rats have no seizures. Electrophysiological recording showed an increased excitatory synaptic transmission and intrinsic membrane excitability in dentate granule cells of the rat hippocampus, together with decreased IA currents and Kv4.2 expression levels. The above results suggest that SESN3 up-regulation may contribute to neuronal hyperexcitability and seizure generation in diabetic animals after ischemia. Further studies are needed to explore the molecular mechanism of SESN3 in seizure generation after ischemia in diabetic conditions.